Balancing Resources and Demand: A Bi-Objective Mixed-Integer Programming Approach of Healthcare Districts in Chile - Quezada-Valenzuela, F; Davila-Galvez, S; Castillo-Contreras, P (Science and Technology Publications, Lda, 2024)
In the search for equitable and efficient health service delivery, geographical partition into operational districts is a fundamental factor. This research delves into the intricate challenge of combinatorial optimization of healthcare districts, with an application to the Metropolitan region of Santiago, Chile, where growing population pressures exacerbate concerns about the distribution of healthcare resources. By emphasizing continuity from primary to secondary healthcare levels, we underline the importance of a good district plan, considering key parameters such as population homogeneity, compactness, and alignment between capacity and demand. By applying a mixed integer linear programming model with a bi-objective function, our findings indicate substantial scope for improving resource allocation, potentially cutting overages by up to 38.77% at the primary healthcare level and up to 15% at the secondary healthcare level. © 2024 by SCITEPRESS - Science and Technology Publications, Lda.